2021
DOI: 10.1001/jamanetworkopen.2021.6069
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Albuminuria in Pediatric Type 2 Diabetes

Abstract: IMPORTANCE Hypertension and albuminuria are markers of diabetes-related nephropathy and important factors associated with kidney outcomes in pediatric type 2 diabetes. However, their prevalence in these patients is unknown. OBJECTIVE To measure the prevalence of hypertension and albuminuria in pediatric patients with type 2 diabetes and to evaluate the association of sex and race/ethnicity with these conditions. DATA SOURCES MEDLINE, Embase, CINAHL, Cochrane Library, Web of Science, the gray literature, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 115 publications
(1,069 reference statements)
0
25
0
Order By: Relevance
“…Evidence indicates, however, that renal involvement in youth onset T2DM occurs early in the disease course, and that progression is similar to that seen in adult T2DM onset [26]. Early manifestation of T2DM renal complication is represented by microalbuminuria, the most commonly reported complication in children and adolescents with T2DM [27]. Estimates vary widely between 7 and 22% at presentation, and between 9.6 and 72% within 3-10 years after diagnosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates, however, that renal involvement in youth onset T2DM occurs early in the disease course, and that progression is similar to that seen in adult T2DM onset [26]. Early manifestation of T2DM renal complication is represented by microalbuminuria, the most commonly reported complication in children and adolescents with T2DM [27]. Estimates vary widely between 7 and 22% at presentation, and between 9.6 and 72% within 3-10 years after diagnosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Another important sign of diabetes-related nephropathy is BP measurement. In pediatric T2DM the guidelines recommend BP and UACR evaluation at diagnosis and annually thereafter[ 58 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Teenagers with T1DM are at risk for hyperfiltration and higher UACR (urinary albumin-to-creatinine ratio), which are biomarkers for early/ incipient nephropathy[ 35 ]. A recent meta-analysis found that almost 25% of T2DM patients have arterial hypertension, the male sex being more frequently affected, and that 1 in 4 or 5 children have albuminuria[ 58 ].…”
Section: Diagnosismentioning
confidence: 99%
“…[9][10][11] At presentation and within the first few years postdiagnosis, patients may develop hypertension, proteinuria, dyslipidaemia, obstructive sleep apnoea, non-alcoholic fatty liver disease and polycystic ovary syndrome. [12][13][14][15] Patients are also predisposed to retinopathy and neuropathy that occur more frequently and earlier in T2DM patients when compared with their T1DM counterparts. 16 There is significant evidence demonstrating that tight glycaemic control improves diabetes…”
Section: Introductionmentioning
confidence: 99%
“…Paediatric T2DM is associated with comorbidities and complications that arise early in the course of the disease 9–11. At presentation and within the first few years postdiagnosis, patients may develop hypertension, proteinuria, dyslipidaemia, obstructive sleep apnoea, non-alcoholic fatty liver disease and polycystic ovary syndrome 12–15. Patients are also predisposed to retinopathy and neuropathy that occur more frequently and earlier in T2DM patients when compared with their T1DM counterparts 16…”
Section: Introductionmentioning
confidence: 99%